2007
DOI: 10.1007/s10753-007-9039-x
|View full text |Cite
|
Sign up to set email alerts
|

Inner Anti-inflammatory Mechanisms of Petroleum Ether Extract from Melilotus suaveolens Ledeb

Abstract: -Summary. Melilotus suaveolens Ledeb is a species of traditional medical plant for treating inflammationrelated disease. This study is to explore the inner anti-inflammatory mechanism on petroleum ether extract from Melilotus suaveolens Ledeb. Materials and Methods. Inflammatory cellular model was founded by intervention of lipopolysaccharide (LPS) on RAW264.7 cell line. Secretion of TNF-a, IL-1b, IL-6, NO and IL-10 in supernatant, mRNA expression of TNF-a, COX-2, iNOS and HO-1, protein expression of COX-2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Kamei et al (36) reported that vincristine administration decreased the levels of NO metabolites, cGMP and protein levels of neuronal NOS in the spinal cord, and a NOS inhibitor reversed the analgesic effect of a NOS substrate, while Bujalska and Gumułka reported that NOS inhibitors prevented the development of hyperalgesia induced by vincristine administration (37). In an inflammatory cellular model, Melilotus extract decreased the secretion of NO and expression of inducible NOS in a dose-dependent manner (38). The role that the effect of Melilotus extract on NO and NOS plays in the treatment of vincristine-induced neuropathy is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Kamei et al (36) reported that vincristine administration decreased the levels of NO metabolites, cGMP and protein levels of neuronal NOS in the spinal cord, and a NOS inhibitor reversed the analgesic effect of a NOS substrate, while Bujalska and Gumułka reported that NOS inhibitors prevented the development of hyperalgesia induced by vincristine administration (37). In an inflammatory cellular model, Melilotus extract decreased the secretion of NO and expression of inducible NOS in a dose-dependent manner (38). The role that the effect of Melilotus extract on NO and NOS plays in the treatment of vincristine-induced neuropathy is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The development of molecular research into inflammation [40,41] prompted us to take LPS-stimulated RAW 264.7 cells as a cell model to explore the molecular anti-inflammatory effects of ethanol extract from K. striata (Thunb.) Schindl ethanol extract on IL-1β, IL-6, IL-10, TNF-α, COX-2 and NFkB.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure has been reported in our previous studies (8). Cells were inoculated into 96-well plate with the density of 1x 10 4 • Each group had 8 wells, and the volume ofeach well was 200 ul, The cells were incubated for 24 h under the condition of 37°C, 5% COz' Then the extracts of cynanchum paniculatum with different concentrations were added.…”
Section: Mrt Assay On Cytotoxicitymentioning
confidence: 99%